1.2.4 Gold/Photocatalyst Dual Catalysis - Barriault,L.; Zidan,M.; Rohe,S. (Dual Catalysis in Organic Synthesis 1, 2020)
The use of gold catalysts in classical two-electron cross-couplings is notoriously impractical due to the high oxidation potential of gold(I)/gold(III) [e.g., E0 (AuI/AuIII) = +1.36 V]. However, when used in tandem with photocatalysts, the gold center can be oxidized one electron at a time, making cross-coupling style reactions with gold more viable. The gold(III) intermediate also has the potential to act as a Lewis acid prior to its reductive elimination step, which has spurred development of multi-bond-forming dual catalytic transformations. This dual-catalytic strategy is also applied in reactions with gold as a photocatalyst in conjunction with an organocatalyst to effectuate traditionally challenging cross couplings.
Keywords: Referencework; photochemistry; Lewis acid catalysts; gold complexes; cross-coupling reactions; diazonium salts; free radicals; tandem reaction